PERANAN KULIAH KERJA NYATA (KKN) MAHASISWA DALAM KEHIDUPAN BERMASYARAKAT - Mufaizah, Mufaizah; Rodiyah, Siti Kholidatur; Ikwan, Mochammad; Mahaphaksi, Mahadma (MAJU : Indonesian Journal of Community Empowerment, 2025)
Community Service Program (Kuliah Kerja Nyata/KKN) is a strategic program that plays a significant role in community empowerment as well as student capacity development. This study examines the role of KKN in community life based on a literature review. The results show that KKN contributes to the development of community potential in the fields of economy, education, and health through innovations brought by students, such as training for small and medium enterprises (SMEs), literacy improvement, and health education.